1999
DOI: 10.1302/0301-620x.81b6.9607
|View full text |Cite
|
Sign up to set email alerts
|

The limping child: epidemiology, assessment and outcome

Abstract: We investigated the epidemiology, assessment and outcome of acute atraumatic limp in 243 children under the age of 14 years presenting to a paediatric accident and emergency department (AED) over a period of six months. Data were collected at presentation and medical notes were re-examined after 18 to 21 months. The incidence of limp was 1.8 per thousand. The male:female ratio was 1.7:1 and the median age 4.35 years. Limp was mainly right-sided (54%) and painful (80%); 33.7% of the children had localised pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
56
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(59 citation statements)
references
References 22 publications
2
56
0
1
Order By: Relevance
“…Ultrasound has been widely advocated as a valuable tool in the assessment of limping children, as it has high sensitivity for diagnosing hip effusion 8,9,11 . However, it is important to remember that it cannot differentiate a reactive effusion from septic arthritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound has been widely advocated as a valuable tool in the assessment of limping children, as it has high sensitivity for diagnosing hip effusion 8,9,11 . However, it is important to remember that it cannot differentiate a reactive effusion from septic arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies comparing different algorithms for assessing acute limp, 1–9 based on combinations of clinical signs, blood inflammatory markers and radiological investigations. There remains considerable variation in recommendations and no consensus as to the best approach.…”
Section: Introductionmentioning
confidence: 99%
“…Difficulty in bearing weight on a leg, characteristic of an acute onset of a limp, suggests the diagnosis of TS [2,3,8,9,13-15] While limitation of internal rotation is the most common finding, referred pain in the knee can occasionally be the predominant complaint [4]. In the reported cases, passive rotations of the hip joint, tested with 90 degrees of hip and knee flexion, were painful.…”
Section: Discussionmentioning
confidence: 99%
“…A UK study reported the incidence of a non-traumatic limp as 1.8 in every 1000 children aged under 14 years, but the true incidence representing all limp is much higher [1]. An 'acute' limp is defined in a patient presenting with symptoms of recent onset, often in the last 48 hours.…”
Section: Introductionmentioning
confidence: 99%